Appraisal of Perspectives to Morality in Business: Towards Developing Effective Operational Mindsets for Business Practitioners - Adewole, Adeyeye; Ginah, Ginah . O. (Advances in Social Sciences Research Journal, 2020)
The study critically examines available perspectives to morality in business. It observes that each of the perspectives to morality in business may seem plausible; the reality of business clearly indicates that morality is intrinsic in the purposes and existence of business. The study further observes that the functional activities of business are pre-supposedly subjects of moral value judgment. The study posits that efforts should rather focus on discussions and concerns on moral benchmarks for sustainable business practices in view of emerging socio-cultural and global dynamics. It concludes that appropriate synthesis of perspectives is the way to go in order to enhance business education among students and practitioners in Nigeria.